New Physics Suggested by Atomki Anomaly - Delle Rose, Luigi; Khalil, Shaaban; King, Simon J. D.; Moretti, Stefano (Frontiers in Physics, 2019)
We consider several extensions of the Standard Model (SM) which can explain the anomalies observed by the Atomki collaboration in the decay of excited states of Beryllium via a new boson with a mass around 17 MeV yielding e+e− pairs. We show how both spin-0 and 1 solutions are possible and describe the Beyond the SM (BSM) scenarios that can accommodate these. They include BSM frameworks with either an enlarged Higgs, or gauge sector, or both.